Teaching gender equality: shifting the focus from aspiration to practice - Rawia Ahmed; M. Fernanda Garcia; Imran Taj; Laila Al Reqabi (Cogent Education)
Purpose This study aims to inform management educators and students about how to identify, analyze, and sustain gender equality as a business practice in organizational settings.Design, Methodology, and Approach Guided by practice theory and social learning theory we: a) offer a theoretical framework to help students recognize gender equality practices in real-world contexts, and b) provide educators with an applied example and pedagogical tool for teaching students how to identify and analyze gender equality practices in written and audio texts. We draw from two theoretical templates to analyze excerpts related to gender equality practices taken from an interview with an MNE business leader based in Latin America conducted by Harvard Business School as part of the Creating Emerging Markets – Oral History Collection Project.Findings Results apply practice theory to the teaching domain and suggest strategies for equipping educators with a tool for informing and sensitizing students regarding gender equality as practice.Originality Unless put into practice, gender equality will continue to lag in implementation in today’s organizations. This paper addresses gender equality as practice and thus equips future business leaders with a necessary understanding of gender equality as practice in written and audio texts in real-world settings. This will help them create and maintain gender equality in their future workplaces and thus become better equipped to manage grand challenges and other complexities in today’s organizations.